2010
DOI: 10.1186/1758-2652-13-37
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to accessing highly active antiretroviral therapy by HIV‐positive women attending an antenatal clinic in a regional hospital in western Uganda

Abstract: BackgroundThe aim of this study was to describe barriers to accessing and accepting highly active antiretroviral therapy (HAART) by HIV-positive mothers in the Ugandan Kabarole District's Programme for the Prevention of Mother to Child Transmission-Plus (PMTCT-Plus).MethodsOur study was a qualitative descriptive exploratory study using thematic analysis. Individual in-depth interviews (n = 45) were conducted with randomly selected HIV-positive mothers who attended this programme, and who: (a) never enrolled in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

25
199
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(226 citation statements)
references
References 26 publications
25
199
2
Order By: Relevance
“…39 Furthermore, in qualitative studies from Malawi, 40 Uganda, 41 and Zimbabwe 42 that examined the reasons for losses to follow-up, the main drivers were found to be the following: long queues at HIV clinics; the cost of transport from homes to clinics; fear of disclosure of HIV status; lack of support from partners who did not want to be tested for HIV; and suggestions on the part of staff to not breastfeed their babies and to feed them formula instead (which was a social taboo). Many of these problems could be alleviated by integrating ART into ANC clinics.…”
Section: Discussionmentioning
confidence: 99%
“…39 Furthermore, in qualitative studies from Malawi, 40 Uganda, 41 and Zimbabwe 42 that examined the reasons for losses to follow-up, the main drivers were found to be the following: long queues at HIV clinics; the cost of transport from homes to clinics; fear of disclosure of HIV status; lack of support from partners who did not want to be tested for HIV; and suggestions on the part of staff to not breastfeed their babies and to feed them formula instead (which was a social taboo). Many of these problems could be alleviated by integrating ART into ANC clinics.…”
Section: Discussionmentioning
confidence: 99%
“…Data on the importance of these factors in ART acceptance have been questionable, with conflicting results between studies. [10,11,[24][25][26][27][28][29][30][31] Partner support was strongly and independently associated with ART initiation among eligible pregnant women in our study, with the odds of initiating ART 4.8-fold higher in women whose partners supported ART initiation compared with those women whose partners did not support ART initiation (p<0.001). Our study contributes to the body of literature that shows that men's support influences women's decisions to accept ART and PMTCT interventions.…”
Section: Discussionmentioning
confidence: 65%
“…Other studies have reported that negative interactions between healthcare staff and pregnant women, negative staff attitudes and poor access to ART services can serve as barriers to the uptake of and adherence to PMTCT services by pregnant women. [6,10,40,42,44,45] …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations